Nanocube Superlattices of Cesium Lead Bromide Perovskites and Pressure‐Induced Phase Transformations at Atomic and Mesoscale Levels. Issue 18 (10th March 2017) - Nagaoka, Yasutaka; Hills‐Kimball, Katie; Tan, Rui; Li, Ruipeng; Wang, Zhongwu; Chen, Ou
Abstract : Lead halide perovskites are promising materials for a range of applications owing to their unique crystal structure and optoelectronic properties. Understanding the relationship between the atomic/mesostructures and the associated properties of perovskite materials is crucial to their application performances. Herein, the detailed pressure processing of CsPbBr3 perovskite nanocube superlattices (NC‐SLs) is reported for the first time. By using in situ synchrotron‐based small/wide angle X‐ray scattering and photoluminescence (PL) probes, the NC‐SL structural transformations are correlated at both atomic and mesoscale levels with the band‐gap evolution through a pressure cycle of 0 ↔ 17.5 GPa. After the pressurization, the individual CsPbBr3 NCs fuse into 2D nanoplatelets (NPLs) with a uniform thickness. The pressure‐synthesized perovskite NPLs exhibit a single cubic crystal structure, a 1.6‐fold enhanced photoluminescence quantum yield, and a longer emission lifetime than the starting NCs. This study demonstrates that pressure processing can serve as a novel approach for the rapid conversion of lead halide perovskites into structures with enhanced properties. Abstract : Pressure processing of CsPbBr3 perovskite nanocube superlattices can generate 2D perovskite nanoplatelets that exhibit a single cubic crystal structure, a 1.6‐fold enhanced photoluminescence quantum yield, and a longer emission lifetime than the starting nanocubes. Pressure processing can serve as a novel approach for the rapid conversion of lead halide perovskites into structures with enhanced structural and optical properties.